(untitled) - Dallas, H. James (Hoboken, 2015)
James Dallas' Mastering the Challenges of Leading Change is an informative, insightful guide to effectively leading the transition through change. While most change management books present case studies about what happened at other companies, this book is based on the author's own experiences managing over 10 transformational and turnaround initiatives, 15 acquisition integrations, and 5 operations/quality shared services centers of excellence. By relating personal lessons learned, how they were subsequently applied, and how you can benefit from them, this book provides a unique first-hand perspective on successful agents of change. You'll learn the qualities and skills required to usher in the new paradigm, and how to break a large initiative into manageable chunks that are more likely to proceed as planned. By crafting your strategy based on proven methods, you're far and away more likely to meet or even exceed your change objectives.
Keywords: Lãnh đạo,Thay đổi tổ chức,Leadership,Organizational change; Quản lý,Management